Numerical assessments of scour depth predictions downstream of box culverts under various flow and blockage conditions - Kaywan Othman Ahmed; Mohammad Reza Kavianpour; Ata Amini; Younes Aminpour (Discover Applied Sciences)
Abstract Ensuring accurate prediction of scour depth in culverts is essential for public safety, as uncertainties in traditional empirical/deterministic equations make it a challenging task. The objective of this study is to investigate the performance of numerical models in predicting the culvert scour’s downstream profile, its maximum depth, and location, prediction was carried out by using Flow-3D software with the Renormalized Group (RNG) turbulence model and comparing these metrics with actual observed data. Two hydrographs were created for unsteady flow, while steady flow conditions were analysed at flow rates of 14 l/s and 22 l/s. The study investigated box culverts with inlet blockages of 0%, 15%, and 30%. The analysis revealed that predictions from numerical models corresponded closely with experimental outcomes, although the scour depths calculated by the models were generally lower than those observed under both steady and unsteady flow conditions. While blockage rates notably impacted scour patterns in the first hydrograph of unsteady flows, increasing blockage percentages did not reliably result in proportional increases in scour depth, as seen in the second hydrograph for unsteady and both steady flow conditions.